Bimbingan Teknis Pengalokasian dan Pembagian Sisa Hasil Usaha Kepada Anggota Sesuai Dengan Prinsip-prinsip Perkoperasian di Koperasi Gula RAFINASI, Kota Yogyakarta - Endang Wahyuningsih (LPPM Universitas Koperasi Indonesia, 2023)
The remaining results of operations is one measure of the success of a business entity. the formation of residual business results is proof of solid cooperation between members as owners as well as customers of cooperatives and cooperative managers who always try to work optimally, effectively, and efficiently. Thus if there is excess/surplus/remaining income after being able to cover all operating expenses and expenses of the cooperative organization, it is only natural that the surplus is allocated to all parties who participate in producing it. Cooperatives are business entities that work with the principles set out in Law No. 25 of 1992, thus in allocating the remaining results of its operations must also be based on the principles it adheres to. In allocating the remaining operating results according to cooperative principles, namely: The distribution of the remaining operating results is carried out fairly in proportion to the amount of business services of each member; Provision of limited remuneration for capital; independence; cooperative member education; cooperation between cooperatives. While the distribution of the remaining results of cooperative operations to members consists of elements, namely the distribution of the remaining results of operations on capital services (contributions) of each member and the distribution of the remaining results of operations on business services (transactions) of each member. Keywords: Remaining Profits (SHU), Cooperative Principles, Allocation and Distribution of SHU